Teacher Strategies for Improving Students’ Questioning Skills in Class - Andawiyah, Robiatul; Masrurah, Waqi'atul; Maimun, Maimun; Hamdani, Hamdani (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
The phenomenon that occurs in learning is based on the lack of students who are interested in asking questions in learning. This is not because students already understand the material being absorbed, but because students do not have the skills to ask questions. The aim of this research is to explore teacher strategies in increasing student asking questions in class. The method used in this research is the library method, by collecting data from relevant literature. The primary source in this research is a study of learning strategies, while the secondary data is from studies that are based on primary sources. The steps taken in the process of collecting data are preparing writing tools, creating a framework, and recording the data obtained. The results of this research are: (1) Before the teacher increases students’ questioning, the teacher must first have the skill of asking questions as part of teaching skills, (2) The teacher creates a stimulus-oriented learning program which in its activities requires a response from students. (3) The strategy for increasing students’ asking questions is by improving the methods used, materials that are appropriate to students’ capacities, language that is easy to understand, and approaching students. The results of this research can contribute to teaching staff in improving students’ skills in asking questions with the solutions offered from the results of this research.